Temporal effect and evolution mechanism of sand-bentonite mixture liner swelling under the influence of sand and diesel - Chun, Ye-yang; Liu, Zhengquan; He, Yong; Wei, He; Su, Dongpo (Frontiers in Materials, 2024)
To elucidate the time-dependent swelling behavior of landfill sand-bentonite mixture liners under the effect of organic pollutants, an no loading swelling ratio test was conducted on mixtures with varying sand and diesel content. The evolution characteristics of the swelling time curve morphology were investigated. The micro-mechanisms underlying the swelling time effect evolution were explored. The results indicated that the sand-diesel interaction significantly altered the swelling time curve morphological characteristics of the mixture. As the sand content increased, the swelling coefficient at the stable state decreased. However, during the rapid swell phase, diesel-contaminated mixed soil does not exhibit the increase-then-decrease pattern in swell coefficient seen in unpolluted mixed soil. The duration of both the slow swelling phase and the time to reach a stable state were longer. Mechanistic analysis revealed that cation exchange capacity is insufficient to effectively analyze the evolution characteristics of the swelling time curve. Instead, the initial swelling potential of bentonite is the true indicator of the mixture's swelling properties. The particle size distribution influences the changes in the swelling coefficient during the rapid swelling phase, but diesel alters the particle size distribution, mitigating its impact. The oil sealing effect within intra-aggregate and inter-aggregate pores not only weakened the swelling characteristics of the mixture at all stages but also increased the permeability resistance, thereby reducing the duration of the rapid swelling phase and extending the slow swelling and stable swelling phases.